Case Report: Guillain−Barré syndrome temporally associated with levofloxacin exposure and improvement following efgartigimod treatment - Xie, Shiyuan; Zhang, Yueling; Shen, Feng; Wu, Lining; Tang, Yunxia; Li, Jun (Frontiers in Immunology, 2026)
Levofloxacin, the L-isomer of the racemic fluoroquinolone ofloxacin, is a broad-spectrum antibiotic with broad clinical applications in both prophylactic and therapeutic indications. However, it has been associated with various adverse reactions, including Guillain−Barré syndrome (GBS). GBS is an immune-mediated peripheral neuropathy that typically presents with acute-onset symmetrical flaccid paralysis. Here, we report a case of GBS temporally associated with levofloxacin exposure that improved after initiation of efgartigimod, following limited response to plasma exchange, methylprednisolone, and intravenous immunoglobulin. To our knowledge, there are no previously published cases of GBS associated with levofloxacin exposure treated with efgartigimod therapy. This case suggests that efgartigimod may represent a promising treatment option for GBS temporally associated with levofloxacin exposure. However, this single case cannot establish efficacy, and delayed responses to prior therapies or spontaneous recovery remain possible alternative explanations. Further studies with larger cohorts are needed to clarify the mechanisms underlying this therapy.